Factors associated with long term work incapacity following a non-catastrophic road traffic injury: analysis of a two-year prospective cohort study - Christopher Papic; Annette Kifley; Ashley Craig; Genevieve Grant; Alex Collie; Ilaria Pozzato; Belinda Gabbe; Sarah Derrett; Trudy Rebbeck; Jagnoor Jagnoor; Ian D. Cameron (BMC Public Health, 2022)
Abstract Background Road traffic injuries (RTIs), primarily musculoskeletal in nature, are the leading cause of unintentional injury worldwide, incurring significant individual and societal burden. Investigation of a large representative cohort is needed to validate early identifiable predictors of long-term work incapacity post-RTI. Therefore, up until two years post-RTI we aimed to: evaluate absolute occurrence of return-to-work (RTW) and occurrence by injury compensation claimant status; evaluate early factors (e.g., biopsychosocial and injury-related) that influence RTW longitudinally; and identify factors potentially modifiable with intervention (e.g., psychological distress and pain). Methods Prospective cohort study of 2019 adult participants, recruited within 28 days of a non-catastrophic RTI, predominantly of mild-to-moderate severity, in New South Wales, Australia. Biopsychosocial, injury, and compensation data were collected via telephone interview within one-month of injury (baseline). Work status was self-reported at baseline, 6-, 12-, and 24-months. Analyses were restricted to participants who reported paid work pre-injury (N = 1533). Type-3 global p-values were used to evaluate explanatory factors for returning to ‘any’ or ‘full duties’ paid work across factor subcategories. Modified Poisson regression modelling was used to evaluate factors associated with RTW with adjustment for potential covariates. Results Only ~ 30% of people with RTI returned to full work duties within one-month post-injury, but the majority (76.7%) resumed full duties by 6-months. A significant portion of participants were working with modified duties (~ 10%) or not working at all (~ 10%) at 6-, 12-, and 24-months. Female sex, low education, low income, physically demanding occupations, pre-injury comorbidities, and high injury severity were negatively associated with RTW. Claiming injury compensation in the fault-based scheme operating at the time, and early identified post-injury pain and psychological distress, were key factors negatively associated with RTW up until two years post-injury. Conclusions Long-term work incapacity was observed in 20% of people following RTI. Our findings have implications that suggest review of the design of injury compensation schemes and processes, early identification of those at risk of delayed RTW using validated pain and psychological health assessment tools, and improved interventions to address risks, may facilitate sustainable RTW. Trial registration This study was registered prospectively with the Australian New Zealand Clinical Trials Registry (ACTRN12613000889752).